Identification and purification of an important cross-reactive allergen from American ( Periplaneta americana) and German ( Blattella germanica) cockroach - Schou, Carsten; Lind, Peter; Fernandez-Caldas, Enrique; Lockey, Richard F.; Løwenstein, Henning (Journal of allergy and clinical immunology, 1990)
Aqueous whole body extracts from two major domiciliary cockroaches, the American, Periplaneta americana, and the German, Blattella germanica were analyzed in crossed immunoelectrophoresis and immunoblotting. Forty-five antigens were found in P. americana and 29 in B. germanica. IgE-binding antigens were identified by crossed radioimmunoelectrophoresis with sera from 30 cockroach-allergic patients. Seven and three precipitates from P. americana and B. germanica bound significant amounts of IgE. A cross-reactive, apparently homologous allergen, from P. americana and B. germanica bound IgE from 100% and 70%, respectively, of the patients. These important allergens were tentatively named Per a I and Bla g I. The allergens were purified by sequential ion exchange, gel filtration, and isoelectric focusing. Both allergens had a molecular size of 33 to 37 kd in Sephadex G-75 gel filtration, and 28 kd in high-performance liquid chromatography gel filtration. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed a minor band at approximately 25 kd, and most of the protein at 6 kd. The isoelectric point of both allergens was found be to 3.5. In amino acid analysis, the allergens were highly similar. Skin test revealed the allergens to be important in vivo sensitizing agents. The allergens may be used for environmental assays for cockroach exposure in the homes of allergic subjects.